2011
DOI: 10.1002/lary.22134
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience in diagnosis and management of superior semicircular canal dehiscence in children

Abstract: In contrast to adults, children with SSCD usually present with auditory symptoms first, although they share some similarities with adults in clinical manifestations of SSCD. Our study shows that SSCD syndrome, a well-accepted clinical entity, exists in the pediatric population. Conservative management is preferred for children with SSCD; nevertheless, surgical intervention is necessary for those with disabling vestibular symptoms. To date, this is the first clinical case series of symptomatic pediatric patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 14 publications
3
38
1
4
Order By: Relevance
“…Auditory complaints were not reported by the patients of the present study as being the first symptoms, however in the literature there are studies in which the patients reported that the first symptoms were the auditory alterations 14 …”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Auditory complaints were not reported by the patients of the present study as being the first symptoms, however in the literature there are studies in which the patients reported that the first symptoms were the auditory alterations 14 …”
Section: Discussioncontrasting
confidence: 63%
“…Such findings are important for the audiological and otoneurological practice, indicating the need to investigate the presence of SSCDS in patients with these symptoms 4,10,11,14 .…”
mentioning
confidence: 95%
“…[13] All of those children with CT-morphological dehiscence did not show any audiological or vestibular symptoms. So far, to our knowledge, there are only two case reports and a case series with a total of seven children with SCD [14][15][16]. The experience with the diagnosis and therapy of dehiscence syndrome in children is limited and still requires standardization.…”
Section: Literature Review and Discussionmentioning
confidence: 84%
“…In the case series presented by Lee, hearing problems were the reason for referral to an ENT specialist [14]. In the above-presented case report, episodes of dizziness were the main complaint made.…”
Section: A Diagnostic Algorithm: History Of Dizziness and Developmentmentioning
confidence: 96%
See 1 more Smart Citation